Development of 6 500 V/200 A High-voltage and High-power Localization IGBT - CHEN Hong; YANG Chunyu; LIU Geli; WU Caisheng; CAO Lin; SUN Jun (机车电传动)
It designed and packed localization IGBT and FRD chip of CRRC. Structural optimization of IGBT was designed through ANSYS simulations of electromagnetic field, heat, stress and so on. The developed IGBT had passed the test of component level, module level, convert level and locomotive class, and satisfy the design requirement. The chip, IGBT, power module to convert industry chain had been formed and successfully used in field of trail transport in China, which has great social signification and market prospect.